Idealisme Perencanaan Keuangan Rumah Tangga Muslim - Saiful Bahri (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2019)
Islamic economics is based on the piety based economy. The piety based economy is reflected in a Muslim's faith in the unseen, establishing prayers, spending part of his wealth fi sabilillah, believing in the Quran and the holy books of Allah which was revealed before the Prophet Muhammad, and believed in the afterlife. Because getting guidance from Allah, in the end, they benefit the world and the hereafter, including fortunate in planning household finances. By using descriptive analysis methods, this study will uncover and produce patterns of consumption, saving considerations, investment and final spending that are ideal for the financial planning of Muslim households.